(untitled) (Bangladesh Critical Care Journal, 2022)
Naphthalene is a widely used industrial and household chemical in the form of mothballs. They are potentially hazardous and rare agents of poisoning. We present a case of ingestional naphthalene poisoning in a G6PD deficient 20 years old male patient with a good outcome after proper management. He presented with abdominal pain, vomiting, fever, passage of dark cola colored urine and jaundice after deliberate ingestion of few mothballs. Features of severe intravascular hemolysis with methemoglobinemia were detected. His G6PD activity was found below normal and was diagnosed as G6PD deficiency disorder. He was treated with IV saline infusion, multiple blood transfusions, IV ascorbic acid and N-acetyl cysteine. He was discharged after 10 days of hospital stay with full recovery. Bangladesh Crit Care J March 2022; 10 (1): 71-74